A new conversation on the existence of Hilfer fractional stochastic Volterra–Fredholm integro-differential inclusions via almost sectorial operators - Sivasankar, Sivajiganesan; Udhayakumar, Ramalingam; Muthukumaran, Venkatesan (Nonlinear Analysis: Modelling and Control, 2023)
The existence of Hilfer fractional stochastic Volterra–Fredholm integro-differential inclusions via almost sectorial operators is the topic of our paper. The researchers used fractional calculus, stochastic analysis theory, and Bohnenblust–Karlin’s fixed point theorem for multivalued maps to support their findings. To begin with, we must establish the existence of a mild solution. In addition, to show the principle, an application is presented.
Keywords: Hilfer fractional system; stochastic system; integro-differential system; almost sectorial operators; multivalued maps